Human-Robot Interaction in Industrial Working Environments: Results from a Start-up Project - António Moniz (Technikfolgenabschätzung – Theorie und Praxis, 2013)
The social dimension of worker-robot interaction in industry is becoming a decisive aspect of robotics development. Many problems and difficulties of robotics research are not only related to technical issues but framed by social aspects. Human-robot interaction (HRI) as a specific research field of robotics tackles this issue. The debate on social involvement in HRI design of a few decades ago must be re-opened. A start-up project was initiated in 2012 at Karlsruhe Institute of Technology (KIT) to define a new research field and establish a conceptual framework on HRI. It was related to recent developments in the manufacturing industry and professional service robotics. The aim was to cooperate with other research teams to establish an expert network in this field. Special focus was placed on the design of work organisation models and issues of robotics technology design for worker (or operator) and robot interaction. In the current paper we present the most important conclusions from these research activities.
Keywords: L6; M11; O33; 330; worker-robot interaction; industry; organisation models